HUBUNGAN EFIKASI DIRI SISWA DENGAN KETERAMPILAN BERKOMUNIKASI SISWA KELAS V SD NEGERI 12 SINGKAWANG - Dandy Fahlavevi; Mariyam; Mertika (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to: 1) Describe the self-efficacy of grade V students at SD Negeri 12 Singkawang. 2) Describe the communication skills of grade V students at SD Negeri 12 singkawang. 3) Knowing whether there is a relationship between students' self-efficacy and the communication skills of grade V students at SD Negeri 12 Singkawang. The type of research used in this study is correlation descriptive research with a quantitative approach with a correlation research design. The population in this study is 59 students in grades VA and VB of SDN 12 Singkawang. The data collection technique in this study is in the form of an adaptation questionnaire from Kurniawati (2016) and Almuhaimin (2014). The data analysis technique is the overall average and the correlation of Pearson product moment. 1) The self-efficacy of students is in the low category with an overall average of 36.82%. 2) Students' communication skills are in the medium category with an overall average of 48.50%. 3) There is a relationship between self-efficacy and students' communication ability which is evidenced based on a significance value of 0.032 < 0.05 with a Pearson Correlation value of 0.809. And it shows a high level of relationship strength. Based on the calculation using the determinant coefficient formula, the relationship between self-efficacy and communication skills of students in elementary school, namely SDN 12 Singkawang, is 65.45%.